Institutional Experience with Spiral Intestinal Lengthening and Tailoring - Coletta, Riccardo; Aldeiri, Bashar; Morabito, Antonino (European Journal of Pediatric Surgery, 2019)
Aim The aim of this study was to report our initial experience using spiral intestinal lengthening and tailoring (SILT) technique in selected cases of short bowel syndrome (SBS).Materials and Methods We analyzed all cases of SBS underwent SILT in our unit since the introduction of the procedure in 2012. We retrospectively analyzed patients' demographics, pre- and postprocedure bowel length, surgical complications, and postoperative parenteral nutrition (PN) requirements. Data were compared using independent samples, Mann–Whitney's U-test.Results Five children with SBS underwent SILT between 2012 and 2017. Median age at procedure was 8.3 months (4.5–16). Preoperative small bowel length measured a median of 22 cm (17.5–50) with a median diameter of 4 cm (3.5–4.6). SILT allowed a median increase in length of 56% (10–15 cm; p = 0.03) and tailoring of the dilated segment providing a reduction in diameter of 50% (4.3–2.1 cm; p = 0.01). No major complications related to SILT were encountered and none of the children required further surgical intervention following a median follow-up of 26 months (14.5–41). Interestingly, we observed a significant reduction of PN requirement at 6 months (p = 0.008) associated with liver function preservation during the follow-up period.Conclusion In our experience, SILT is a promising adjunct in the surgical management of SBS. It can be used to tailor and lengthen mildly dilated segments of the bowel where other procedures are technically challenging, with a view to reduce the risk of intestinal failure associated liver disease and thereby improving chances for quality survival. Further studies are needed to investigate long-term outcomes of SILT in pediatric SBS.
Keywords: short bowel syndrome; intestinal lengthening; reconstructive surgery